4-Chloro-N-(3-chlorophenyl)benzenesulfonamide - Shakuntala, K. (International Union of Crystallography, 2011)
In the crystal of the title compound, C(12)H(9)Cl(2)NO(2)S, the molecule is twisted at the S atom with a C—SO(2)—NH—C torsion angle of −58.4 (3)°. Furthermore, the N—H bond in this segment is anti to the meta-chloro group. The dihedral angle between the aromatic rings is 77.1 (1)°. The crystal structure features inversion-related dimers linked by N—H⋯O hydrogen bonds.